Integrated Processing of Secondary Raw Materials as the Main Direction of Ecologization of Beet Sugar Production In The Republic of Kazakhstan - Zhaxygulova, Gulzira; Myrzabekova, Maiya; Sadykova, Guzel (EDP Sciences, 2020)
Beet sugar production is one of the material-intensive industries, where the volume of raw and auxiliary materials used in production is several times higher than the output of finished products. It is also a source of multi-tonnage secondary resources, i.e. by-products and production waste, the main ones beingAbeet pulp, molasses and filtration sludge. Against the background of the implementation of the Sectoral Program of Beet Sugar Production Development in the Republic of Kazakhstan for 2018-2027, there is a need to create a concept of ecologization of production, which will provide for the development of fundamentally new technologies to ensure minimum waste, combining environmentally friendly methods with cost-effective production of sugar beet and by-products. The bet should be made on low-cost technologies that will minimize production costs and environmental impact. In this article possible variants of sugar beet processing technologies with complex deep processing of waste are offered. The comparison of traditional technology and various variants of progressive technologies of sugar beet processing and production of new products from secondary resources was carried out, which allowed to determine revenue from complex processing of 1 ton of sugar beet.
Keywords: Environmental sciences; Beet Sugar; GE1-350; Secondary Raw Materials; Kazakhstan; 2. Zero hunger; 8. Economic growth; 7. Clean energy; 12. Responsible consumption